2019
DOI: 10.1017/dsi.2019.198
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Virtual Reality and Desktop Interface for Reviewing 3D CAD Models

Abstract: Use of virtual reality (VR) is considered beneficial for reviewing 3D models throughout product design. However, research on its usability in the design field is still explorative, and previous studies are often contradictory regarding the usability of VR for 3D model review. This paper argues that the usability of VR should be assessed by analysing human factors such as spatial perception and taking into consideration the complexity of the reviewed product. Hence, a comparative evaluation study has been condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
1
38
0
1
Order By: Relevance
“…We have not attempted to measure the level of design understanding achieved by participants, although it was noted that there were no issues in relation to this in terms of discussion or assessment during the sessions. The suggestions in the literature that VR models can provide clearer benefits in relation to high-complexity models (Horvat et al, 2019) were not applicable to the products used in our cases, although it did prove useful in the examination of surface contours; this is an issue worth considering in a comparative or more quantitative study. However, the discussion below draws on the presence ratings, participant feedback and researcher observation to highlight the main insights in terms of the VR interface and experience or participants.…”
Section: Data Collectionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have not attempted to measure the level of design understanding achieved by participants, although it was noted that there were no issues in relation to this in terms of discussion or assessment during the sessions. The suggestions in the literature that VR models can provide clearer benefits in relation to high-complexity models (Horvat et al, 2019) were not applicable to the products used in our cases, although it did prove useful in the examination of surface contours; this is an issue worth considering in a comparative or more quantitative study. However, the discussion below draws on the presence ratings, participant feedback and researcher observation to highlight the main insights in terms of the VR interface and experience or participants.…”
Section: Data Collectionmentioning
confidence: 87%
“…Some of these are more developed than othersworkflows for porting 3D design geometry require optimization, and an accessible, dynamic VR CAD environment requires careful reconfiguration. There are significant levels of potential benefit, however, particularly in the interrogation of more complex CAD geometry (Horvat et al, 2019). Widening scope to also consider AR and MR highlights a range of other relevant researcha comprehensive reviews by Nee et al (2012) and Bottani and Vignali (2019) highlight a range of AR and MR applications in design in manufacturing settings.…”
mentioning
confidence: 99%
“…Results showed that the estimation of the model dimensions was enhanced when IVR was used. Furthermore, in the same study, scholars also reported that differences between a desktop interface and IVR for reviewing models were more evident for 3D CAD models of higher complexity levels [17]. In architectural design, Paes et al [24] conducted an experiment that included asking the participants to identify correct values of spatial properties (such as dimensions, proportions, and apertures) of an entrance hall of the building presented in IVE, nIVE, and physical environment.…”
Section: ) Studies Of Perception Of Spatial Propertiesmentioning
confidence: 99%
“…Another finding was that participants in the IVE overestimated the depth value for all the models that were used in the experiment. The comparative study done by Horvat et al [17] assessed engineering students' spatial perception of 3D CAD models of products with different levels of complexity while reviewing them using IVR technology and conventional 2D user interface. Participants were asked to verbally estimate the size of the models' dimensions.…”
Section: ) Studies Of Perception Of Spatial Propertiesmentioning
confidence: 99%
See 1 more Smart Citation